Preparation method of antimony / diindium trisulfide sodium storage negative electrode material
By carbon coating on indium trisulfide and building a heterostructure of antimony/indium trisulfide, the volume expansion, diffusion kinetics and conductivity problems of the negative electrode material of sodium ion battery are solved, and high specific capacity and cycle are achieved Improved stability.
Patent Information
- Application Number
- CN202411316332.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The sodium ion battery negative electrode material indium trisulfide has problems such as huge volume expansion, slow sodium ion diffusion kinetics and low conductivity, which limits its application performance.
By carbon coating on disulfide and building a heterostructure of antimony/disulfide trisulfide, its conductivity and reactivity are enhanced, and the ratio of antimony and disulfide trisulfide is regulated to improve capacity and cycling stability.
It effectively alleviates volume changes during charging and discharging, reduces ion diffusion resistance, promotes redox reaction, improves specific capacity and rate performance, and significantly improves the transmission rate of sodium ions and electrons.
Smart Images

Figure CN119191340A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an indium trisulfide sodium storage negative electrode material. Background Art
[0002] Sodium-ion batteries are considered to be one of the most promising next-generation batteries in the future, thanks to the abundant sodium reserves in the earth and the similar working principle to lithium batteries. However, the current negative electrode materials of sodium-ion batteries face two major problems: sluggish kinetics and large volume expansion. Therefore, the development of a low-cost, high-performance negative electrode material is the key to the application of sodium-ion batteries.
[0003] Transition metal sulfides have attracted much attention due to their high specific capacity and abundant redox reaction sites, and are very promising candidate materials for negative electrodes of sodium-ion batteries. Among them, indium sulfide has attracted widespread attention due to its high theoretical specific capacity and low discharge platform. However, its ion storage capacity has been limited by the huge volume expansion, slow sodium ion diffusion kinetics and low conductivity in the application process. Summary of the invention
[0004] The present invention aims to solve the technical problems of huge volume expansion, slow sodium ion diffusion kinetics and low conductivity of indium trisulfide, a negative electrode material for sodium ion batteries, and provide a method for preparing an antimony / indium trisulfide sodium storage negative electrode material.
[0005] The preparation method of the antimony / indium trisulfide sodium storage negative electrode material of the present invention is carried out according to the following steps:
[0006] S1, mixing the methanol solution and the N,N-dimethylformamide solution to obtain a uniform solution;
[0007] The volume ratio of methanol to N,N-dimethylformamide is (6-9):1;
[0008] S2, adding indium salt and thioacetamide to the uniform solution of S1 successively, wherein the concentration of indium salt is 0.01mol / L-0.05mol / L, and the concentration of thioacetamide is 0.1mol / L-0.5mol / L; then stirring magnetically for 12h-14h, adding imidazole and continuing stirring for 2h-3h to obtain a milky white solution, wherein the concentration of imidazole is 0.05mol / L-0.06mol / L;
[0009] S3, transferring the milky white solution in S2 to a high-pressure reactor for solvothermal reaction, filtering and drying in sequence to obtain a precursor; ultrasonically dissolving the precursor in a Tris solution to obtain a solution A;
[0010] The concentration of the Tris solution is 0.1 mol / L to 0.15 mol / L;
[0011] The mass ratio of the precursor to the volume of the Tris solution is 8g:(5L-6L);
[0012] S4, adding dopamine hydrochloride to solution A, and continuing stirring for 6 h to 7 h to obtain solution B;
[0013] The molar ratio of the amount of dopamine hydrochloride to the precursor prepared in S3 is 1:1;
[0014] S5, filtering and washing the solution B prepared in S4, and drying it in a vacuum oven to obtain carbon-coated indium trisulfide;
[0015] S6, dispersing the carbon-coated indium trisulfide and antimony trichloride prepared in S5 in anhydrous ethanol respectively, and subjecting them to ultrasonic treatment to obtain solution C and solution D respectively;
[0016] S7, adding solution D dropwise into the heated and stirred solution C, continuing heating and stirring for 30 min to 40 min, then centrifugally washing for multiple times, vacuum drying, and finally calcining under protective gas to obtain an antimony / indium trisulfide heterostructure;
[0017] The heating temperature is 60℃~65℃;
[0018] The calcination temperature is 500°C to 550°C, and the calcination time is 2h to 3h;
[0019] The molar ratio of antimony trichloride in solution D to carbon-coated indium trisulfide in solution C is 1:(1-4).
[0020] Principle of the invention: The theoretical specific capacity of indium trisulfide is 658 mAh g -1 , in the electrochemical conversion process of the sodium ion battery, indium trisulfide shows a significant volume change, and there is a large volume expansion, which leads to the failure of the electrode structure. The present invention enhances the conductivity of indium trisulfide by carbon coating (the carbon source is dopamine hydrochloride), and reduces the volume strain during the sodium conversion reaction. At the same time, since the theoretical specific capacity of antimony is higher, the introduction of antimony can significantly increase the capacity of the sample, and the unification of capacity and cycle stability can be achieved by reasonably regulating the ratio of antimony and indium trisulfide. The present invention can not only promote the generation of internal electric field, but also enhance the activity of electrochemical reaction at the heterogeneous interface by constructing a heterostructure of antimony element and indium trisulfide, thereby improving the transmission rate of sodium ions and electrons, and then obtaining high specific capacity and rate performance.
[0021] The beneficial effects of the present invention are as follows: the present invention effectively alleviates the problem of severe volume change of negative electrode materials of sodium batteries during charge and discharge, resulting in unsatisfactory cycle stability, through the ingenious design of heterogeneous structures. The present invention increases the lattice defects on the surface by designing the heterogeneous interface of metal sulfides to obtain abundant active sites. The method of the present invention not only reduces the diffusion resistance of ions and promotes rapid redox reactions, but also provides more sites for electrochemical reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the antimony / indium trisulfide heterostructure prepared in Experiment 1;
[0023] Figure 2 This is the SEM image of the antimony / indium trisulfide heterostructure prepared in Experiment 2;
[0024] Figure 3 SEM image of indium trisulfide prepared for comparative test;
[0025] Figure 4 XRD pattern of the antimony / indium trisulfide heterostructure prepared in experiment 1;
[0026] Figure 5 This is the charge and discharge curve of the battery assembled with the product of experiment one as the negative electrode in experiment three;
[0027] Figure 6 This is a comparison chart of cycle performance. DETAILED DESCRIPTION
[0028] Specific implementation method 1: This implementation method is a method for preparing an antimony / indium trisulfide sodium storage negative electrode material, which is specifically carried out according to the following steps:
[0029] S1, mixing the methanol solution and the N,N-dimethylformamide solution to obtain a uniform solution;
[0030] The volume ratio of methanol to N,N-dimethylformamide is (6-9):1;
[0031] S2, adding indium salt and thioacetamide to the uniform solution of S1 successively, wherein the concentration of indium salt is 0.01mol / L-0.05mol / L, and the concentration of thioacetamide is 0.1mol / L-0.5mol / L; then stirring magnetically for 12h-14h, adding imidazole and continuing stirring for 2h-3h to obtain a milky white solution, wherein the concentration of imidazole is 0.05mol / L-0.06mol / L;
[0032] S3, transferring the milky white solution in S2 to a high-pressure reactor for solvothermal reaction, filtering and drying in sequence to obtain a precursor; ultrasonically dissolving the precursor in a Tris solution to obtain a solution A;
[0033] The concentration of the Tris solution is 0.1 mol / L to 0.15 mol / L;
[0034] The mass ratio of the precursor to the volume of the Tris solution is 8g:(5L-6L);
[0035] S4, adding dopamine hydrochloride to solution A, and continuing stirring for 6 h to 7 h to obtain solution B;
[0036] The molar ratio of the amount of dopamine hydrochloride to the precursor prepared in S3 is 1:1;
[0037] S5, filtering and washing the solution B prepared in S4, and drying it in a vacuum oven to obtain carbon-coated indium trisulfide;
[0038] S6, dispersing the carbon-coated indium trisulfide and antimony trichloride prepared in S5 in anhydrous ethanol respectively, and subjecting them to ultrasonic treatment to obtain solution C and solution D respectively;
[0039] S7, adding solution D dropwise into the heated and stirred solution C, continuing heating and stirring for 30 min to 40 min, then centrifugally washing for multiple times, vacuum drying, and finally calcining under protective gas to obtain an antimony / indium trisulfide heterostructure;
[0040] The heating temperature is 60℃~65℃;
[0041] The calcination temperature is 500°C to 550°C, and the calcination time is 2h to 3h;
[0042] The molar ratio of antimony trichloride in solution D to carbon-coated indium trisulfide in solution C is 1:(1-4).
[0043] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the indium salt described in S2 is indium sulfate. Other aspects are the same as those of specific embodiment 1.
[0044] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the temperature of the solvent thermal reaction in S3 is 85° C. and the reaction time is 72 h. Other aspects are the same as specific embodiment 1 or 2.
[0045] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the drying condition in S3 is: drying in a vacuum oven for 6 hours. The rest is the same as specific embodiments 1 to 3.
[0046] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the filtration in S5 needs to be washed three times with water and anhydrous ethanol respectively, and then dried in a vacuum oven at 60° C. for 6 hours. Others are the same as specific embodiment 4.
[0047] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that the vacuum drying in S7 is: drying in a vacuum oven at 60° C. for 6 hours. The rest is the same as specific embodiment 5.
[0048] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the protective gas in S7 is argon gas. Other aspects are the same as specific embodiment 6.
[0049] Specific implementation example eight: This implementation example is different from specific implementation example seven in that the heating rate described in S7 is 2°C / min. The rest is the same as specific implementation example seven.
[0050] The present invention is verified by the following tests:
[0051] Experiment 1: This experiment is a method for preparing an antimony / indium trisulfide sodium storage negative electrode material, which is specifically carried out in the following steps:
[0052] S1, mixing the methanol solution and the N,N-dimethylformamide solution to obtain a uniform solution;
[0053] The volume ratio of methanol to N,N-dimethylformamide is 7:1;
[0054] S2, indium sulfate and thioacetamide are successively added to the uniform solution of S1, wherein the concentration of indium sulfate is 0.02 mol / L, and the concentration of thioacetamide is 0.15 mol / L; then the reaction is carried out by magnetic stirring for 12 hours, and imidazole is added and stirred for 2 hours to obtain a milky white solution, wherein the concentration of imidazole is 0.05 mol / L;
[0055] S3, transferring the milky white solution in S2 to a high-pressure reactor for solvothermal reaction, filtering and drying in sequence to obtain a precursor; ultrasonically dissolving the precursor in a Tris solution to obtain a solution A;
[0056] The temperature of the solvothermal reaction was 85 °C and the reaction time was 72 h;
[0057] The concentration of the Tris solution is 0.1 mol / L;
[0058] The mass ratio of the precursor to the volume of the Tris solution is 8 g:5 L;
[0059] The drying conditions were: drying in a vacuum oven for 6 h;
[0060] S4, adding dopamine hydrochloride to solution A, and stirring continuously for 6 hours to obtain solution B;
[0061] The molar ratio of the amount of dopamine hydrochloride to the precursor prepared in S3 is 1:1;
[0062] S5, filtering and washing the solution B prepared in S4, and drying it in a vacuum oven to obtain carbon-coated indium trisulfide;
[0063] The filtrate needs to be washed three times with water and anhydrous ethanol respectively, and then dried in a vacuum oven at 60°C for 6 h;
[0064] S6, 0.05 mmol of carbon-coated indium trisulfide prepared in S5 and 0.0125 mmol of antimony trichloride were dispersed in 10 mL of anhydrous ethanol, and subjected to ultrasonic treatment to obtain solution C and solution D, respectively;
[0065] S7, adding solution D dropwise into the heated and stirred solution C, continuing heating and stirring for 30 min to 40 min, then centrifugally washing for multiple times, vacuum drying, and finally calcining under argon protection to obtain an antimony / indium trisulfide heterostructure;
[0066] The vacuum drying is: drying in a vacuum oven at 60°C for 6 hours;
[0067] The heating temperature is 60°C;
[0068] The calcination temperature is 550°C, the calcination time is 2h, and the heating rate is 2°C / min.
[0069] Experiment 2: This experiment differs from Experiment 1 in that the amounts of carbon-coated indium trisulfide and antimony trichloride in S6 are both 0.0125 mmol. Other aspects are the same as Experiment 1.
[0070] Comparative test: This test does not add elemental antimony. The specific process is different from that of test 1: there is no S6.
[0071] S7, calcining the carbon-coated indium trisulfide prepared in S5 under argon protection to obtain indium trisulfide. Other steps are the same as those in Experiment 1.
[0072] Figure 1 This is the SEM image of the antimony / indium trisulfide heterostructure prepared in experiment 1. Figure 2 This is the SEM image of the antimony / indium trisulfide heterostructure prepared in Experiment 2. Figure 3 The SEM image of indium trisulfide prepared for the comparative experiment shows that the introduction of antimony did not significantly change the morphology of the material. All three products are spherical and covered with small particle protrusions on the surface.
[0073] Experiment 3: The negative electrode materials (calcined products) prepared in the above three experiments were prepared into button batteries according to the button battery process, and the process was as follows, and the test was carried out:
[0074] The negative electrode materials prepared in the three experiments were mixed evenly with the conductive agent and the binder in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone was added and ground, and then evenly coated on the Cu foil. After being completely dried, the Cu foil coated with the slurry was punched with a hole punch to form a pole piece with a diameter of 12 mm as the negative electrode, a sodium sheet with a diameter of 14 mm as the counter electrode, and glass fiber as the battery separator. The button batteries were assembled in a glove box filled with argon in the order of pole piece, separator and sodium sheet.
[0075] The test results of the three batteries are shown in Table 1 below.
[0076] Figure 4 This is the XRD pattern of the antimony / indium trisulfide heterostructure prepared in experiment 1. It can be seen from the figure that the antimony / indium trisulfide heterostructure was successfully prepared.
[0077] Combined with Table 1 Figure 2 It can be seen that the combination of antimony and indium trisulfide significantly improves the first-cycle discharge capacity, and when the molar ratio of indium trisulfide to antimony is 4:1, its cycle stability and charge and discharge capacity are optimal.
[0078] Table 1
[0079]
[0080] Figure 5 This is the charge and discharge curve of the battery assembled with the product of experiment 1 as the negative electrode in experiment 3. It can be seen that the capacity of the first cycle in the first five cycles of charge and discharge curves reaches 715.5 mAh g -1 The curves have a high degree of overlap during the charge and discharge process, indicating that the sample capacity has a high reversibility.
[0081] Figure 6 The red line is the battery assembled with the product of experiment 1 as the negative electrode in experiment 3, the blue line is the battery assembled with the product of experiment 2 as the negative electrode in experiment 3, the yellow line is the battery assembled with the product of the comparative experiment as the negative electrode in experiment 3, and the green Coulomb efficiency is the battery assembled with the product of experiment 1 as the negative electrode in experiment 3. It can be seen that the battery assembled with the product of experiment 1 as the negative electrode has a high reversible capacity and significant cycle stability. The discharge capacity after 350 cycles is 387.8 mAh g -1 The capacity decay rate at the 350th cycle was 0.13%, and the capacity retention rate was significantly higher than that of other materials.
Claims
1. A method for preparing an antimony / indium trisulfide sodium storage negative electrode material, characterized in that The preparation method of the antimony / indium trisulfide sodium storage negative electrode material is carried out according to the following steps: S1, mixing the methanol solution and the N,N-dimethylformamide solution to obtain a uniform solution; The volume ratio of methanol to N,N-dimethylformamide is (6-9):1; S2, adding indium salt and thioacetamide to the uniform solution of S1 successively, wherein the concentration of indium salt is 0.01mol / L-0.05mol / L, and the concentration of thioacetamide is 0.1mol / L-0.5mol / L; then stirring magnetically for 12h-14h, adding imidazole and continuing stirring for 2h-3h to obtain a milky white solution, wherein the concentration of imidazole is 0.05mol / L-0.06mol / L; S3, transferring the milky white solution in S2 to a high-pressure reactor for solvothermal reaction, and successively filtering and drying to obtain a precursor; The precursor is dissolved in a Tris solution by ultrasonication to obtain solution A; The concentration of the Tris solution is 0.1 mol / L to 0.15 mol / L; The mass ratio of the precursor to the volume of the Tris solution is 8g:(5L-6L); S4, adding dopamine hydrochloride to solution A, and continuing stirring for 6 h to 7 h to obtain solution B; The molar ratio of the amount of dopamine hydrochloride to the precursor prepared in S3 is 1:1; S5, filtering and washing the solution B prepared in S4, and drying it in a vacuum oven to obtain carbon-coated indium trisulfide; S6, dispersing the carbon-coated indium trisulfide and antimony trichloride prepared in S5 in anhydrous ethanol respectively, and subjecting them to ultrasonic treatment to obtain solution C and solution D respectively; S7, adding solution D dropwise into the heated and stirred solution C, continuing heating and stirring for 30 min to 40 min, then centrifugally washing for multiple times, vacuum drying, and finally calcining under protective gas to obtain an antimony / indium trisulfide heterostructure; The heating temperature is 60℃~65℃; The calcination temperature is 500°C to 550°C, and the calcination time is 2h to 3h; The molar ratio of antimony trichloride in solution D to carbon-coated indium trisulfide in solution C is 1:(1-4).
2. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The indium salt described in S2 is indium sulfate.
3. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The temperature of the solvothermal reaction in S3 was 85 °C and the reaction time was 72 h.
4. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The drying conditions in S3 are: drying in a vacuum oven for 6 hours.
5. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The filtrate in S5 needs to be washed three times with water and anhydrous ethanol respectively, and then dried in a vacuum oven at 60°C for 6 h.
6. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The vacuum drying in S7 is: drying in a vacuum oven at 60° C. for 6 h.
7. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The protective gas described in S7 is argon.
8. The method for preparing an antimony / indium trisulfide sodium storage negative electrode material according to claim 1, characterized in that The heating rate in S7 is 2°C / min.
